Wybrane aspekty audytu środków unijnych - Sawicka-Kluźniak, Zofia (Selected Aspects of European Union Funds Audit, 2009)
The estimation of correctness in using European Union funds is the assignment of the external auditor. The audit of these funds is based both on national and foreign regulations. The audit of the structural funds relies on examining the system of management and control
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 288-298